Persepsi Masyarakat Mengenai Penanganan Krisis Event Musik (Studi Kasus Festival Berdendang Bergoyang) - Mufid, Jazil Abdul; Alvansa, Moch; Sultana, Reyhan Daffa (COMMUSTY Journal of Communication Studies and Society, 2022)
This study aims to determine the public's views or perceptions of handling the crisis at the organizers of the "Berdendang Bergoyang" music event held on October 30 2022 at the open field of Istora Senayan. This research was conducted on the public and the audience who knew about the event's failure. The problem of this research is failure and confusion. The research method used is qualitative by conducting interviews with the community. However, based on the data obtained from the interviews conducted, the public viewed the festival negatively based on the news spread on social media. This study uses the theory from David Ewen which discusses the world of music and is developed by researchers into a problem at events related to music.